Dengue Outbreak in Pakistan: Status, Challenges and way Forward - Qidwai, Waris (Journal of Liaquat University of Medical & Health Sciences, 2019)
Dengue is vectorborne viral infection transmitted to humans by the female Aedes aegypti mosquito. Infection with dengue virus may result either in an asymptomatic infection or a febrile illness of varying severity ranging from mild illness to more severe forms such as dengue hemorrhagic fever and dengue shock syndrome 2. At global level, there has been a reported 30fold increase in incidence of Dengue in previous five decades 1. Recent Dengue outbreak in Pakistan has reached epidemic proportion and has surpassed all previous records. Previous large outbreak occurred in 2011 and affected 27,000 people across the country including 370 deaths. During the current year over 25,000 dengue cases have been confirmed from across the country. This includes 6, 537, 5, 642, 4, 403, 4, 276 2, 750 cases from Islamabad, Punjab, Sindh, Khyber Pakhtunkhwa and Bal ochi stan respectively.